1995
DOI: 10.1017/s1357729800008249
|View full text |Cite
|
Sign up to set email alerts
|

Effects of artificial photoperiods on sexual behaviour and sperm output in the rabbit

Abstract: Male rabbits aged from 4 to 4-5 months were subjected to a 8L : 16D photoperiod for 4 weeks and were then split into two groups. One group of13 males was maintained at 8L : 16D (group 8). The other included 16 males and was submitted to 16L : 8D (group 16). Two successive ejaculates zvere collected and analysed once a week for 6 months. Animals from group 8 were sexually more active and ejaculated significantly larger volumes of semen than those from group 16. Performance of males from group 16 was better for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 6 publications
2
13
0
Order By: Relevance
“…Concerning the influence of the rank of the ejaculate on semen characteristics, the higher mass motility found in the second ejaculate is in agreement with the results of Bencheikh [6] and Theau-Clément et al [27]. Several authors have found a higher concentration and production of spermatozoa in the second ejaculate [6,12,21,23,27].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Concerning the influence of the rank of the ejaculate on semen characteristics, the higher mass motility found in the second ejaculate is in agreement with the results of Bencheikh [6] and Theau-Clément et al [27]. Several authors have found a higher concentration and production of spermatozoa in the second ejaculate [6,12,21,23,27].…”
Section: Discussionsupporting
confidence: 87%
“…Several authors have found a higher concentration and production of spermatozoa in the second ejaculate [6,12,21,23,27]. Our study did not allow verification of this since concentration was never recorded on both ejaculates from one buck and moreover it was only recorded on a selected sample of the ejaculates.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Thirty adult (7 months of age) New Zealand White rabbit bucks were divided into three homogeneous groups and submitted to 3 rhythms of semen collection: every day (D), every week (W) and every 2 weeks (2W). Rabbits were kept under a continuous 16 h light/8 h dark photoperiod (Theau-Clément et al, 1995) with an intensity of 40 lux (Besenfelder et al, 2005). The ambient temperature ranged from 18 to 27°C.…”
Section: Animals and Housingmentioning
confidence: 99%
“…However, these animals selected for high growth rate usually present a relatively low sperm count (200-600 × 10 6 ), the number of inseminations per week being reduced to 10 or 20 (the main authors advise around 16-30 × 10 6 spermatozoa per insemination). Several studies have thus been carried out to increase the number of doses and quality of the sperm produced per male, reducing the number of sperm in insemination doses [1] or improving male management [2][3][4].…”
Section: Introductionmentioning
confidence: 99%